(untitled) (Singaporean Journal of Business Economics and Management, 2017)
The current study aims to examine the moderating role of employees trust on the relationship of transformational leadership and workforce deviance. Four telecom operators were selected for data collection from twin cities of Pakistan, and 233 sample was chosen on random bases and data collected from lower, middle and top level employees working in four telecom operators. By using SPSS 20.0, moderated hierarchical regression applied to examine the role of employees trust on the relationship of transformational leadership and organizational deviance. The statistical results of the currents reveal that there is negative and significant correlation exist between transformational leadership and organizational deviance. Moreover, the statistical analyses of hierarchical multiple regression also reveal that employees trust significantly moderates the relationship between transformational leadership and organizational deviance. The transformational leadership relates with organizational outcomes i.e. higher followers’ commitment, citizenship behaviors, job satisfaction and lower workplace deviance. This study also concludes that organizational efforts foster transformational leadership fruitfully. In addition, trust-based climate can foster the likelihood of lower workplace deviance and transformational leadership. Furthermore, by incorporating transformational leadership apart from authentic leadership also contributes to positive follower outcomes is a new call. This call has opposed that trust and high quality leader-follower fellowship can be a fundamental link to transformational leader behavior. This relationship is not investigated empirically in Pakistan context till date.